2017
DOI: 10.1093/sf/sox041
|View full text |Cite
|
Sign up to set email alerts
|

The Globalization of Production and Income Inequality in Rich Democracies

Abstract: Despite prominent and compelling theoretical arguments linking manufacturing imports from the global South to rising income inequality in the global North, the literature has produced decidedly mixed support for such arguments. We explain this mixed support by introducing intervening processes at the global and national levels. At the global level, evolving characteristics of global production networks (GPNs) amplify the effect of Southern imports. At the national level, wage-coordination and welfare state gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 46 publications
4
54
0
Order By: Relevance
“…While some scholars disagree on the magnitude of the effect of international trade on income distribution (Krugman and Lawrence ), and others question whether international trade has an effect at all (Babones and Vonada ), some research found international trade to increase inequality in advanced industrial countries (Kerrissey ; Kwon ; Mahutga et al. ).…”
Section: National Income Inequality and Globalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…While some scholars disagree on the magnitude of the effect of international trade on income distribution (Krugman and Lawrence ), and others question whether international trade has an effect at all (Babones and Vonada ), some research found international trade to increase inequality in advanced industrial countries (Kerrissey ; Kwon ; Mahutga et al. ).…”
Section: National Income Inequality and Globalizationmentioning
confidence: 99%
“…However, research investigating the potential impact of imports from the Global South on inequality in 18 advanced industrial countries found that Southern imports increases income inequality only in countries with above‐average levels of integration in the global market and relatively strong wage‐bargaining institutions and welfare state generosity (Mahutga et al. ). This finding shows that although Southern imports may increase national income inequality in advanced economies, the process varies across countries.…”
Section: National Income Inequality and Globalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, I investigate what factors have shaped the distribution of income during the early 2000s. While scholars often restrict attention to affluent nations (Kollmeyer, 2015; Kwon, 2016; Mahutga et al, 2017), I build on prior work that examines inequality in a global context (Cole, 2015; Kerrissey, 2015; Lee, 2005a, Lee et al, 2007; Wong, 2016). In doing so, I employ a large cross-national sample (1284 observations across 129 countries) covering a more recent time period relative to previous work (2000–2015), using the latest version of the Standardized World Income Inequality Database (SWIID v8.0).…”
Section: Introductionmentioning
confidence: 99%
“…What needs to be done now is another update of the tests for long-term effects of dependence on foreign investment to see if the negative effects found for earlier decades are still present. Tausch's prescient warnings regarding the potential for negative effects of investment dependence on core countries seem to have been borne out in the years since his article was published (Mahutga, Roberts and Kwon 2017). An interesting recent article by economist Dani Rodrik (2018) observes that the neoliberal globalisation project produced left-wing populist movements in Latin America (the so-called Pink Tide) and right-wing populist movements in Europe.…”
mentioning
confidence: 99%